Legal Smoke and Mirrors: Unmasking Indonesia’s Climate Crisis Policies and Regulations - Wijaya Kusuma, Daffa Prangsi Rakisa; Ardhany, Yustika; Mustafa, Ahmed (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
This study critically examines Indonesia's climate crisis policies and regulations, aiming to unveil the obscured intricacies within the existing legal framework. The metaphorical smoke and mirrors represent the complex and potentially deceptive nature of the country’s approach to addressing the climate crisis. Employing a meticulous analysis, the research dissects the substance and effectiveness of current policies, seeking to unmask potential gaps and contradictions. The study scrutinizes the alignment between stated objectives and practical outcomes, aiming to expose any discrepancies and provide a comprehensive understanding of Indonesia’s climate governance. As climate change becomes an increasingly urgent global concern, understanding the efficacy of national policies becomes paramount. By unraveling the layers of Indonesia's climate crisis policies, this research offers valuable insights for policymakers, scholars, and activists engaged in environmental advocacy. The findings aim to inform future legislative efforts, encouraging a more transparent, effective, and integrated approach to climate crisis mitigation and adaptation. Ultimately, the study serves as a critical resource for those navigating the complex landscape of climate governance, fostering awareness and facilitating informed decision-making in the pursuit of sustainable solutions.